2007
DOI: 10.2478/v10003-007-0005-2
|View full text |Cite
|
Sign up to set email alerts
|

Tree-Ring Chronologies of Downy Oak (<i>Quercus Pubescens</i>), Pedunculate Oak (<i>Q. Robur</i>) and Sessile Oak (<i>Q. Petraea</i>) in the Bielinek Nature Reserve: Comparison of the Climatic Determinants of Tree-Ring Width

Abstract: for the two indigenous oak species pedunculate and sessile oak, respectively. These chronologies were used for signature years and response function analyses. All three chronologies were highly similar, which points to identical responses to the ambient meteorological conditions. The radial increment of downy oak depends primarily on the amount of precipitation. A high annual sum of precipitation, copious rain in springsummer in particular, results in wide tree rings. Precipitation in form of rain and snow in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 7 publications
4
29
0
3
Order By: Relevance
“…The effect of autumn and winter climatic factors on the formation of carbohydrate storage has been proven repeatedly (Lebourgeois et al, 2004;Cedro, 2007;Doležal et al, 2010;Petráš and Mecko, 2011;Michelot et al, 2012). In the area we studied, we mainly found an effect of the January climate: negative correlations were found for temperatures (mean, maximum, and minimum) and vapor pressure deficit; positive correlations were found for relative moisture and relative saturation of the soil profile in the top 40 cm.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…The effect of autumn and winter climatic factors on the formation of carbohydrate storage has been proven repeatedly (Lebourgeois et al, 2004;Cedro, 2007;Doležal et al, 2010;Petráš and Mecko, 2011;Michelot et al, 2012). In the area we studied, we mainly found an effect of the January climate: negative correlations were found for temperatures (mean, maximum, and minimum) and vapor pressure deficit; positive correlations were found for relative moisture and relative saturation of the soil profile in the top 40 cm.…”
Section: Discussionmentioning
confidence: 64%
“…Some of the characteristics also manifested significant correlations in July, August, and September ( Table 3). The significant positive effect of precipitation in May and June has also been proven by a number of European dendroclimatological and xylogenetic studies dealing with the sessile oak in France (Becker et al, 1994;Lebourgeois et al, 2004;Mérian et al, 2011;Michelot et al, 2012), Romania (Popa et al, 2013), Germany (Friedrichs et al, 2009), Slovakia (Petráš andMecko, 2011), Poland (Cedro, 2007;Bronisz et al, 2012), and Moravia, Czech Republic (Doležal et al, 2010). The negative effect of June (or July) temperatures has also been demonstrated repeatedly (Doležal et al, 2010;Mérian et al, 2011;Petráš and Mecko, 2011;Michelot et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many authors found that the radial growth of pines and oaks, the most important forest tree species, growing outside the mountain areas in Poland, is mainly limited by the pre-growth season temperature (e.g., Wazny and Eckstein 1991;Zielski 1997;Cedro 2004Cedro , 2007SzychowskaKrąpiec 2010;Bronisz et al 2012;Koprowski et al 2012;Muter 2012). For both these taxons cold and frosty winters, low temperatures in early spring and dry summers are disadvantageous (in particular, all of these factors acting together) (Feliksik and Wilczyński 1998;Wilczyński 1999;Cedro 2007;Szychowska-Krąpiec 2010;Bronisz et al 2012). Although the period of cambial activity of pine begins in early May and lasts until the end of September, the annual growth of wood is also affected by climatic conditions in winter preceding the growth season (Ermich 1959).…”
Section: Introductionmentioning
confidence: 99%
“…The growth pattern and growth-climate responses of pear trees in Bielinek are very similar to the chronology for downy oak Quercus pubescens Willd. on the same site: Student's t of 7.9, correlation coefficient of 0.46, and Gl of 74% (Cedro, 2007(Cedro, , 2013. The similarity of complex chronologies for pear trees in Bielinek and Biedrusko is much lower: Student's t of 4.6, correlation coefficient of 0.43, and Gl of 57% (Fig.…”
Section: Discussionmentioning
confidence: 99%